Durum wheat and allelopathy: toward wheat breeding for natural weed management - Fragasso, Mariagiovanna; Iannucci, Anna; Papa, Roberto (Frontiers in Plant Science, 2013)
Wheat-derived foodstuffs represent about one-fifth of the calories consumed by humans worldwide. Bread wheat (Triticum aestivum L.) is one of the most important crops throughout the world, and it has been extensively studied for its allelopathic potential. In contrast, for allelopathy in durum wheat (Triticum turgidum ssp. durum), our knowledge is partial and fragmentary. Through highlighting recent advances in using allelopathy as a crop breeding tool, we provide an overview of allelopathy in Triticum spp., to stimulate further coordinated breeding-oriented studies, to favour allelopathy exploitation for the sustainable cultivation of wheat, and in particular, to achieve improved biological weed control.